Rak piersi w ciąży - odmienności procesu diagnostyki i leczenia = Breast cancer during pregnancy - differences in diagnostic and treatment procedures - Magdalena Sowa; Iwona Głowacka; Paulina Wardęcka; Andrzej Winnicki (Kazimierz Wielki University, 2016)
Sowa Magdalena, Głowacka-Mrotek Iwona, Wardęcka Paulina, Winnicki Andrzej. Rak piersi w ciąży - odmienności procesu diagnostyki i leczenia = Breast cancer during pregnancy - differences in diagnostic and treatment procedures. Journal of Education, Health and Sport. 2016;6(9):586-596. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155058 http://ojs.ukw.edu.pl/index.php/johs/article/view/3884         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Rak piersi w ciąży - odmienności procesu diagnostyki i leczenia Breast cancer during pregnancy - differences in diagnostic and treatment procedures   Magdalena Sowa1, Iwona Głowacka-Mrotek2, Paulina Wardęcka3, Andrzej Winnicki4   1Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Laseroterapii i Fizjoterapii, Katedra Chirurgii Onkologicznej 2Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Klinika Rehabilitacji 3Wojewódzki Szpital Specjalistyczny im. księdza Jerzego Popiełuszki we Włocławku, Oddział Ginekologiczno - Położniczy 4 Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Technologii Postaci Leku     Adres do korespondencji: Magdalena Sowa Katedra i Zakład Laseroterapii i Fizjoterapii Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Ul. Techników 3 85 -801 Bydgoszcz e - mail: magdalena.sowa@cm.umk.pl         Streszczenie Wprowadzenie: Rak piersi w ciąży jest rozpoznawany stosunkowo rzadko. W ostatnich dziesięciu latach w Europie można zauważyć wyraźną tendencję do odraczania macierzyństwa wśród młodych kobiet. Obecnie średnia wieku kobiet rodzących pierwsze dziecko wynosi 30 lat. Jednym z czynników ryzyka zachorowania na raka piersi jest wiek. Z uwagi na fakt, iż kobiety coraz później decydują się na macierzyństwo, a średnia wieku występowania raka piersi się obniża,  z tą szczególną sytuacją kliniczną lekarzom jak i kobietom przyjdzie się zmagać coraz częściej.  Cel pracy:Celem pracy była próba przybliżenia odmienności procesu diagnostyki i leczenia raka gruczołu piersiowego rozpoznanego w ciąży. Rozwinięcie:Z danych epidemiologicznych wynika, iż rak piersi jest najczęściej występującym nowotworem u kobiet ciężarnych.Szczególnie niebezpiecznym jest fakt, iż zmiany fizjologicznie zachodzące w organizmie kobiety już od pierwszych tygodni ciąży, mogą maskować pojawienie się guza i znacznie opóźniać wdrożenie procesu diagnostyki.  Choroba nowotworowa rozpoznana w czasie trwania ciąży jest zawsze dramatyczną i ogromnie stresującą sytuacją dla kobiety i jej najbliższych, dlatego proces diagnostyki i leczenia jest silnie zindywidualizowany, zaś maksymalny efekt terapeutyczny z jednoczesną ochroną nienarodzonego dziecka stanowi priorytet działań. Podsumowanie:Decyzje terapeutyczne podejmowane są po uwzględnieniu ogólnego stanu zdrowia pacjentki, stopnia zaawansowania klinicznego nowotworu, wieku ciążowego oraz postulatów samej pacjentki i jej najbliższych.W niniejszej pracy, posługując się metodą analizy piśmiennictwa szczegółowo omówiono odmienności w procesie diagnostyki i leczenia raka piersi u kobiet ciężarnych.   Słowa kluczowe: rak piersi, ciąża, diagnostyka, leczenie   Breast cancer during pregnancy - differences in diagnostic and treatment procedures Abstract Introduction: Breast cancer during pregnancy is relatively rare. There has been an increasing trend for young women to delay childbearing for the last ten years. Presently the average age of first-time mothers is 30. Age is one of the factors increasing the risk of breast cancer. The defined clinical situation will appear more often considering the fact that women delay their motherhood where as the average age of breast cancer decreases. Objective: The purpose of this article is to present different diagnostic and treatment procedures of breast cancer diagnosed during pregnancy. Main text: The analysis of epidemiological data points the fact breast cancer is the most often appearing one in pregnant women. The fact that physiological changes in females during pregnancy first weeks may mask cancer is particularly dangerous and may essentially delay diagnostic procedures. Cancer diagnosed during pregnancy is always a traumatic and stressful situation for a woman and her family that is why its diagnostic and treatment procedures are considerably individualized whereas the maximum terapeutical effect with the protection of an unbornchild is the priority of activities. Summary: Therapeutic decisions are made after a review of a health condition of a patient, the extent of spread of cancer, gestational age and demands of the patient and her family. In the article, undertaking a literature review, alternative breast cancer diagnostic and treatment procedures during pregnancy were discussed in details.   Key words: brest cancer, pregnancy, diagnostics procedures, treatment